M?_ssbauer spectrometry of A2FeMoO6 (A =Ca, Sr, Ba): Search for antiphase domains - VENKATESAN, MUNUSWAMY; COEY, JOHN MICHAEL DAVID (American Physical Society, 2001)
M?_ssbauer spectrometry was carried out in the range of temperature from 4 K to well above the Curie temperature on polycrystalline ceramics of A2FeMoO6 (A=Ca,Sr,Ba). A secondary component in all the paramagnetic or ferromagnetic spectra is attributed to iron in the vicinity of a defect in the NaCl-type cation order. The secondary component and the lack of saturation of the magnetization at the half metallic value of 4 ?_B/formula unit are explained in terms of antisite defects (point defects) and antiphase boundaries (planar defects). The point defects predominate in all three compounds, but there is some evidence of antiphase boundaries from the spectrum of the Ca compound in a 6 T applied field. The dimensions of the antiphase domains are estimated to be of order 0.5 ?_m. The electronic configuration of iron in the Ca and Sr compounds is close to 3d5.2, whereas it is 3d5.5 in the Ba compound.
PUBLISHED
Keywords: Physics